1970
DOI: 10.1104/pp.46.3.423
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between the Kinetics of Ribonucleic Acid Accumulation and the Morphological Development of the Fern Gametophyte, Dryopteris borreri

Abstract: Fern gametophytes were grown under blue light with and without the addition of 5-fluorouracil or 8-azaguanine, and under red light. Nucleic acids were extracted by either the detergent-chloroform or the detergent-diethylpyrocarbonate method and analyzed by polyacrylamide gel electrophoresis. No significant differences in the relative distribution of the stable RNA components accompanied the transition to biplanar growth. The RNA content per average cell decreased with growth and also varied between the cultura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1972
1972
1983
1983

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…After 4 days in red light, the radioactive pattern was similar to that observed prior to the shift. (3,10,25,27,28).…”
Section: Methodsmentioning
confidence: 99%
“…After 4 days in red light, the radioactive pattern was similar to that observed prior to the shift. (3,10,25,27,28).…”
Section: Methodsmentioning
confidence: 99%
“…mode and time course of photomorphogenesis) and biochemical differences {i.e. extractability of rRNA) between D. borreri and D. filixmas which these workers have themselves reported Ingle 1970, Ingle andBurns 1968). Since a change in the total-RNA base composition has been shown for D. erythrosora (Table 1 and Hotta 1960); and since a decrease in nucleolar size (Bergfeld 1967) and an increase in chloroplast size (Bergfeld 1963) have been shown to accompany the transition from filamentous to prothallial growth in D. filix-mas, it would be interesting to have such data from D. borreri.…”
Section: Discussionmentioning
confidence: 96%
“…This is consistent with the observation that chloramphenicol, presumed to have its primary effect on protein synthesis in the chloroplasts, did not prevent this photomorphogenetic transition (Bergfeld 1968). Burns and Ingle (1970) have recently reported that there is no change in the relative amount of chloroplast and cytoplasmic rRNAs during photomorphogenesis in unsterilized cultures of Dryopteris borreri. In addition these workers found that the chloroplast rRNA level did Table 3.…”
Section: Discussionmentioning
confidence: 99%
“…However, little attention was paid to this point in previous works (SCHRAUDOLI MILLER, 1968;BURNS andINGLE, 1968, 1970;DAVIS, 1968DAVIS, , 1970SCHRAUDOLF and LEGLER, 1969;HOWLAND, 1972). On the contrary, the influences of the inhibitors o n the orientation of the cell plate were successfully examined for the first time under a microscope using an appropriate experimental system.…”
Section: Discussionmentioning
confidence: 99%
“…BEKCFELD (1964) also pointed out that much of the blue-light-induced protein synthesis resulted from chloroplast development. Lately, evidence has accumulated against the hypothesis (SOBOTA andPARTANW, 1966, 1967;SCHRAUDOLF, 1967;MILLER, 1968;DAVIS, 1968DAVIS, , 1970BURNS andINGLE, 1968,1970;SCHRAUDOLF and LEGLER, 1969;HOWLAND, 1972).…”
mentioning
confidence: 99%